Berardinelli - Seip Congenital Lipodystrophy - An infantile presentation - Nayak, Snehamayee (Indian Journal of Case Reports, 2015)
Berardinelli – Seip congenital lipodystrophy (BSCL) is an inherited form of generalized lipodystrophy characterized by loss of subcutaneous fat, hypertriglyceridemia, insulin resistance and acanthosis nigricans. Rare cases of BSCL type 2 present during infancy or early childhood. It is caused by mutation in Seipin gene. It is a severe phenotype with premature death occurring in 15% cases. We present such a rare case of BSCL in a five month old infant.